Humoral and Cell-Mediated Responses to SARS-CoV-2 Vaccination in a Cohort of Immunodeficient Patients - Federica Plano; Mojtaba Shekarkar Azgomi; Anna Maria Corsale; Corinne Spoto; Nadia Caccamo; Serena Meraviglia; Francesco Dieli; Paolo D’Angelo; Antonino Trizzino; Sergio Siragusa (Hematology Reports, 2023)
This study delves into the intricate landscape of SARS-CoV-2 vaccine response in immunodeficient patients, focusing on the dynamics of both humoral and cell-mediated immunity. The cohort includes patients with common variable immunodeficiency (CVI), agammaglobulinemia (XLA), and combined immunodeficiency (CI). The findings reveal varying degrees of antibody production, with XLA patients exhibiting no measurable response but displaying a robust T-cell-mediated response. The study emphasizes the importance of considering both arms of the immune system in assessing vaccine immunogenicity, particularly in the context of immunodeficiency. The results challenge conventional measures of vaccine efficacy only based on antibody titers, highlighting the need for a more comprehensive understanding of the immune response in this vulnerable population. This research contributes valuable insights to guide clinical decisions regarding vaccination strategies, booster doses, and overall protection in immunodeficient individuals.